Synthesis and characterization of secondary and ternary ammonium based protic ionic liquids for thermoelectrical cell / Tawsif Ahmed Siddique - Tawsif Ahmed , Siddique (2016)

(untitled)
The ability to efficiently harvest heat as a source of sustainable energy would make a significant contribution to reduce our current reliance on fossil fuels. Waste heat sources, such as those produced in industrial processes or through geothermal activity, are extensive, often continuous, and at present severely underutilised. Thermoelectrochemical cells offer an alternative design to the traditional semiconductor-based thermoelectric devices and offer the promise of continuous and cheap operation at moderate temperatures, low maintenance and with no carbon emissions. They utilize two electrodes, held at different temperatures, separated by an electrolyte containing a redox couple. It is the temperature dependence of the electrochemical redox potential that generates the potential difference across the device as a result of the applied temperature difference. The magnitude of this redox potential temperature dependence is given by the Seebeck coefficient, Se. The organic sector is showing promising growths along with good environmental impact nowadays. Until recently, research into TEC cells had primarily focused on aqueous media. However, the good thermal and electrochemical stability, non-volatility and non-flammability of many ionic liquids make them promising alternative electrolytes for these devices. The use of ionic liquid (IL) electrolytes offers potential advantages that include increased TEC device efficiencies, lifetimes and the ability to utilize low temperature (often “waste”) heat sources in the 100 – 200ºC temperature range. This research is targeted to explore the potentiality of protic ionic liquids in thermoelectric research. In this study, total eight of two series of PILs based on secondary and/or tertiary ammonium cations with the trifluoroacetate, methanesulfonate, trifluoromethanesulfonate and tosylate anions were synthesized for TEC cells. PILs based electrolyte coupled with I-/I3- redox couple have been investigated as thermoelectric materials. In addition, the thermal and physical properties have also been investigated as these PILs are the new addition in the list of PILs. The complete study on PILs has been done to determine the nature and efficiency for thermoelectricity. The investigation carried out the thermal energy between the range of room temperature and 90 °C. PILs shows lower thermal conductivity and good ionic conductivity which enables to succeed good thermoelectric materials. As a great achievement, our proposed PILs shows higher Se values 420 μV/K obtained for TEHA TFMS than the reported values of the same redox couple. The excellent dimensionless figure of merit value, ZT (949.46×10-6) has been achieved by BEHA TFMS. The power and the current output of the studied PILs are higher than some aprotic ionic liquids reported.